Assessing the efficiency and eco-sustainability of bioremediation strategies for the reclamation of highly contaminated marine sediments. (December 2020) - Dell'Anno, A.; Beolchini, F.; Corinaldesi, C.; Amato, A.; Becci, A.; Rastelli, E.; Hekeu, M.; Regoli, F.; Astarita, E.; Greco, S.; Musco, L.; Danovaro, R.
Abstract: Coastal sediments subjected to high anthropogenic impacts can accumulate large amounts of polycyclic aromatic hydrocarbons (PAHs) and metals, demanding effective and eco-sustainable remediation solutions. In this study, we carried out bioremediation experiments on marine sediments highly contaminated with PAHs and metals. In particular, we investigated the effects of biostimulation (by the addition of inorganic nutrients), bioaugmentation (by the addition of fungi belonging to Aspergillus sp.) and microbial fuel cell-based strategies on PAH degradation and on changes in metal partitioning. Results reported here indicate that all biotreatments determined a significant decrease of PAH concentrations (at least 60%) in a relatively short time interval (few weeks) and that biostimulation was the most effective approach (>90%). Biostimulation determined a faster degradation rate of high than low molecular weight PAHs, indicating a preferential biodegradation of specific PAH congeners. At the same time, the biotreatments changed the partitioning of metals, including their solubilization, suggesting the need of parallel environmental risk assessment. Our findings also suggest that ex situ biotreatments can have a lower carbon footprint than current management options of contaminated sediments (i.e., landfill disposal and/or disposal in confined aquatic facilities), but integration with other strategies for metal removal (e.g. through bioleaching) from sediments is needed for their safe re-use. Overall, results presented here provide new insights into the development of effective and eco-sustainable bioremediation strategies for the reclamation of highly contaminated marine sediments. Graphical abstract: Image 1 Highlights: Effective and sustainable remediation solutions for contaminated sediments are needed. Different biotreatments are effective to reduce significantly PAH contamination. Biostimulation can induce a preferential biodegradation of specific PAH congeners. Biotreatments may increase the ecotoxicological risk due to metal leaching. Biotreatments can have a lower carbon footprint than current management options.